2017
DOI: 10.1108/rpj-02-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Edge quality in fused deposition modeling: II. experimental verification

Abstract: Purpose-To provide an experimental evaluation of geometric errors on the edges of parts manufactured by the FDM process. Design/methodology/approach-An experimental plan was conducted by building parts in ABS thermoplastic resin on a commercially available machine with given combinations of the three geometric variables (inclination, included and incidence angle) defined in the first part of the paper. Edges on built parts were inspected on a 2D non-contact profilometer to measure position and form errors. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
(37 reference statements)
0
10
0
1
Order By: Relevance
“…Results showed a close relationship between surface finish, with build direction. Armillotta and Cavallaro (2017) proposed an empirical model to forecast the existence of visible imperfections on the edges of a part before manufacturing it with a given build orientation (Armillotta et al , 2017a). Alsoufi and Elsayed (2017) investigated the influence of factors on the surface finish of parts made up of PLA+ material and found that layer height and nozzle diameter were significant in terms of part surface roughness.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Results showed a close relationship between surface finish, with build direction. Armillotta and Cavallaro (2017) proposed an empirical model to forecast the existence of visible imperfections on the edges of a part before manufacturing it with a given build orientation (Armillotta et al , 2017a). Alsoufi and Elsayed (2017) investigated the influence of factors on the surface finish of parts made up of PLA+ material and found that layer height and nozzle diameter were significant in terms of part surface roughness.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Selain porositas, proses pendinginan yang tidak seragam pada proses pencetakan FDM juga menjadi masalah yang dapat menyebabkan penyusutan yang tidak seragam [23]. Akibat dari fenomena ini, muncul efek anak tangga pada bagian permukaan hasil FDM dengan menggunakan sudut raster tertentu [24]. Terbatasnya penelitian pada penggunaan material TPE mendorong dilakukannya penelitian ini untuk mendukung kemajuan teknologi FDM.…”
Section: Pendahuluanunclassified
“…In general, a smaller LH results in higher ultimate tensile strength and Young’s modulus [ 27 ]. In addition, the surface quality is optimized by smaller LH in terms of the staircase-effect and dimensional accuracy [ 28 , 29 ]. A larger LH leads to lower mechanical properties [ 27 ] and coarse surface qualities like increased waviness [ 28 ] or the staircase effect [ 2 ], but reduces the manufacturing time [ 19 ].…”
Section: Introductionmentioning
confidence: 99%